Prevalence of dysfunctional breathing in patients treated for asthma in primary care: cross sectional survey - Thomas, Mike (BMJ, 2001)
OBJECTIVES: To estimate the prevalence of dysfunctional breathing in adults with asthma treated in the community. DESIGN: Postal questionnaire survey using Nijmegen questionnaire. SETTING: One general practice with 7033 patients. PARTICIPANTS: All adult patients aged 17-65 with diagnosed asthma who were receiving treatment. MAIN OUTCOME MEASURE: Score ⩾23 on Nijmegen questionnaire. RESULTS: 227/307 patients returned completed questionnaires; 219 (71.3%) questionnaires were suitable for analysis. 63 participants scored ⩾23. Those scoring ⩾23 were more likely to be female than male (46/132 (35%) v 17/87 (20%), P=0.016) and were younger (mean (SD) age 44.8 (14.7) v 49.0 (13.8, (P=0.05). Patients at different treatment steps of the British Thoracic Society asthma guidelines were affected equally. CONCLUSIONS: About a third of women and a fifth of men had scores suggestive of dysfunctional breathing. Although further studies are needed to confirm the validity of this screening tool and these findings, these prevalences suggest scope for therapeutic intervention and may explain the anecdotal success of the Buteyko method of treating asthma.